The Relationship between Learning Activities and Mathematical Problem-Solving Abilities in Elementary School - Febrianti, Inda; Prasetyo, Teguh; Hayu, Wiworo Retnadi Rias; Chongbang , Nirmal; Kumar , Komil (EDUPEDIA Publisher, 2023)
This research investigates the relationship between elementary school students' learning activities and mathematical problem-solving abilities. A quantitative functional correlation method was utilized with 52 fourth-grade students. Questionnaires were used to measure learning activities, while problem descriptions were used to assess mathematical problem-solving abilities. The IBM SPSS Statistics 22.0 application and the Spearman Rank method were used for data analysis. The study results indicate a positive relationship between learning activities and mathematical problem-solving abilities. The regression equation showed a proportional relationship, where higher learning activities resulted in better problem-solving abilities. The coefficient of determination indicated that 8.2% of the variance in problem-solving abilities could be attributed to learning activities. The t-test results demonstrated a significant relationship between learning activities and mathematical problem-solving abilities. Therefore, this study concludes that learning activities significantly impact the mathematical problem-solving abilities of fourth-grade elementary school students in Banjarwatu, Bogor Regency.